About the environmental sustainability of the European management of WEEE plastics. (1st May 2021) - Cardamone, Giovanni Francesco; Ardolino, Filomena; Arena, Umberto
Graphical abstract: Highlights: Three current scenarios of WEEE plastics management in Europe have been analysed. An LCA study quantified the environmental performances of main WEEP treatments. The maximum WEEP recovery rates have been estimated for each category and polymer. Styrenics show lowest recovery rates due to the high content of Br-compounds. Results show dramatic contributions of WEEP exportation and its improper treatments. Abstract: A huge increase of waste of electrical and electronic equipment (WEEE) is observing everywhere in the world. Plastic component in this waste is more than 20% of the total and allows important environmental advantages if well treated and recycled. The resource recovery from WEEE plastics is characterised by technical difficulties and environmental concerns, mainly related to the waste composition (several engineering polymers, most of which containing heavy metals, additives and brominated flame retardants) and the common utilisation of sub-standard treatments for exported waste. An attributional Life Cycle Assessment quantifies the environmental performances of available management processes for WEEE plastics, those in compliance with the European Directives and the so-called substandard treatments. The results highlight the awful negative contributions of waste exportation and associated improper treatments, and the poor sustainability of the current management scheme. The ideal scenario of complete compliance with European Directives is the only one with an almost negligible effect on the environment, but it is far away from the reality. The analysed real scenarios have strongly negative effects, which become dramatic when exportation outside Europe is included in the waste management scheme. The largely adopted options of uncontrolled open burning and illegal open dumping produce huge impacts in terms of carcinogens (3.5·10 +7 and 3.6·10 +4 person⋅year, respectively) and non-carcinogens (1.7·10 +8 and 2.0·10 +6 person⋅year) potentials, which overwhelm all the other potential impacts. The study quantifies the necessity of strong reductions of WEEE plastics exportation and accurate monitoring of the quality of extra-Europe infrastructures that receive the waste.